Changes in cold-related mortalities between 1995 and 2016 in South East England - Donaldson,GC; Witt,C; Näyhä,S (Public Health, 2019)
OBJECTIVE: The aim of the study was to examine trends in cold-related mortalities between 1995 and 2016. STUDY DESIGN: This is a longitudinal mortality study. METHODS: For men and women aged 65-74 years or those older than 85 years in South East England, the relationship between daily mortality (deaths per million population) and outdoor temperatures below 18 °C, with allowance for influenza epidemics, was assessed by linear regression on an annual basis. The regression coefficients were expressed as a percentage of the mortality at 18 °C to adjust for changes in mortality through health care. Trends in 'specific' cold-related mortalities were then examined over two periods, 1977-1994 and 1995-2016. RESULTS: In contrast to the early period, annual trends in cold-related specific mortalities showed no decline between 1995 and 2016. 'Specific' cold-related mortality of women, but not men, in the age group older than 85 years showed a significant increase over the 1995-2016 period, which was different from the trend over the earlier period (P < 0.01). CONCLUSION: Despite state-funded benefits to help alleviate fuel poverty and public health advice, very elderly women appear to be at increasing risk of cold-related mortality-greater help may be necessary.